VIABILITAS DAN KERIAP Bacillus sp. BK17 DAN Enterobacter sp. BK15 PADA SUMBER KARBON DAN NITROGEN YANG BERBEDA - Sirma Novita Nasrah; Dwi Suryanto; It Jamilah (Saintia Biologi, 2012)
To propagate bacterial cell for biocontrol purpose, suitable nutrient have to be determined in which carbon and nitrogen source was often as limited factor of bacterial growth. Proper storage for biocontrol agent such as bacterial cell should also be considered in order to keep the cell viable when used. The aim of this study is to find out suitable carbon and nitrogen sources for viability and swarming of chitinolitic bacterial Bacillus sp. BK17 and Enterobacter sp. BK15. The highest population of bacterial growth (3.7x108 cfu/ml) was found in molases-sodium nitrate (MS) medium and the lowest population was found in crab shell-sodium nitrate (CS) growth (2.4x108 cfu/ml) after 25 days of incubation. The swarming activity of the isolates were varied to some extent with the highest was 51 mm in 2% agar molases-urea after 5 days of incubation. Molases-sodium nitrate (MS) medium is suitable carbon and nitrogen source for the viability of Bacillus sp. and Enterobacter sp. Meanwhile, agar molases-urea medium with 2% agar is suitable medium for swarming ability for both bacteria. Keywords : Bacillus, C and N-source, Enterobacter, swarming, viability